O processo administrativo das instituições financeiras à luz da Lei nº. 13.506/2017 - Costa, Pedro Luiz Chagas (2021)
The present dissertation has the nodal point of examining the administrative sanctioning law that applies to financial institutions within the scope of the Central Bank of Brazil. This is because, after the enactment of Law no. 13,506 / 2017, the theme gained a legal framework, with several innovations in relation to the text of the fifty-year old Law no. 4.595/64 that regulated the matter until then and, in addition to being out of time, has fundamental gaps in the subject of the sanctioning law, by failing to address issues such as the procedural rite, typology of infractions and the possibility of using consensual instruments. The consequence of these gaps was the issuance of several rules of an infra legal nature that ended up guiding the sanctioning process at the Central Bank, which was overcome with the promulgation of the new law. Thus, after analyzing the evolution in sanction law in Brazil and how this sphere of administrative law ceases to have a purely retributive role to have an instrumental character, the work focuses on analyzing the innovations presented by the new legal text, as well as its weak points that still need evolution, together with proposals to overcome these weaknesses. Then, the study presents in detail the main advance of the legislative text, consisting of the inclusion of conciliation instruments within the scope of the sanctioning law of the Central Bank of Brazil. Finally, the survey presents the main positions of the Brazilian Courts and the Appeals Council of the National Financial System regarding the application of the new legislation. With this, the research can conclude that the theme presents a striking legislative, doctrinal and jurisprudential evolution, as well as that the penalties applied until the present moment, did not incur the weak points of the legislation. However, the research points out that the precedents studied so far are subject to the political pluralism of the public authorities, as well as that there are themes in the legislation that still cause legal uncertainty to the administrators